Kinematic and muscle co-activation patterns in the dominant arm across forehand stroke phases in wheelchair tennis - Khaled Abuwarda; Abdel-Rahman Akl (Frontiers in Bioengineering and Biotechnology)
ObjectiveThis study investigated upper limb kinematics and muscle co-activation in wheelchair tennis players during the forehand stroke. By analyzing linear and angular kinematic variables alongside muscle co-activation patterns, the study aimed to provide insights into the biomechanical mechanisms supporting forehand stroke performance.MethodFifteen professional male wheelchair tennis players (height: 163.9 ± 2.05 cm; mass: 64.1 ± 3.07 kg; age: 32.2 ± 7.97 years) participated in this study. Electromyographic data from six muscles around the dominant arm joints were recorded using the Myon system. Four fixed GoPro Hero 8 cameras (120 Hz) captured 3D video, and kinematic analyses were performed using the APAS system. The forehand stroke was analyzed across three phases: (1) backswing, (2) forwardswing, and (3) follow-through.ResultsThe results showed significant phase-specific changes in muscle co-activation for the shoulder (p < 0.001), elbow (p < 0.005), and wrist (p < 0.01). Muscle co-activation was highest during the backswing phase, decreased during the forwardswing, and increased again during the follow-through phase. This pattern reflects the need for joint stability and control, particularly when changing stroke direction and slowing the arm after impact.ConclusionThese findings provide novel insights into the kinematic and neuromuscular mechanisms underlying the forehand stroke in wheelchair tennis. The data provide hypotheses about potential training and rehabilitation strategies that should be tested by prospective studies. The results also highlight the unique demands of wheelchair tennis, contributing to inclusive, evidence-based approaches to enhancing performance and safety in disability sports.